Board structure and corporate disclosure via social media: an empirical study in the UK. Issue 5 (15th August 2018) - Basuony, Mohamed A.K.; Mohamed, Ehab K.A.; Samaha, Khaled
Abstract : Purpose: The purpose of this paper is to investigate the impact of board structure on voluntary corporate disclosure via social media among the top 150 companies listed on the London Stock Exchange. Design/methodology/approach: A disclosure index comprising of a set of items that encompass two facets of disclosure, namely corporate disclosure via social networks and social media sites, is developed and used. Binary logistic regression is used to test the research hypotheses. Findings: The results of this study reveal the underlying relations between board composition and control variables as the determining factors of corporate disclosure, i.e. board size, board activism, board independence and board diversity (gender and ethnicity). The gender of the board can affect the corporate disclosure via a social network. The results of this study indicate that an increase in the number of female in the board members leads to higher corporate disclosure using social network. Moreover, firm size has a positive effect on corporate disclosure indicating that large firms tend to disclose more information on their websites and social networks. Practical implications: The paper provides new insights into the role played by the non-executive female directors in monitoring and controlling managerial processes related to corporate disclosure using social media. Originality/value: To the best of the authors' knowledge, this is the first paper that examines the role of board structure in monitoring and controlling management decisions and managerial processes in the area of corporate disclosure via social media.